Using citizen notification to interrupt near-repeat residential burglary patterns: the micro-level near-repeat experiment - Groff, Elizabeth (Journal of experimental criminology, 2019)
Test the efficacy of swift resident notification for preventing subsequent burglaries within near-repeat high-risk zones (NR-HRZ).